OPTIMALISASI FASILITAS WISATA DALAM MEMBANGUN PERKEMBANGAN PARIWISATA PANTAI DI DESA DADAP KECAMATAN SAMBELIA, KABUPATEN LOMBOK TIMUR - Jurnal Wicara; I Made Oka Aditya; Elivia Novela Sari; Yunika Latifatunnupus; Muhammad Faisal Dzaky Yudistira; Ni Luh Trisna Sutriatiningsih; M. Zamzami; Iswatun Husaini; Silvia Yuliana; Khairunnisak (Universitas Mataram, 2023)
Dadap Village has tourism potential that is still not well known by the wider community. Several contributing factors are that tourism in Dadap village has not been utilized properly, the location of the village is far from the city, and the lack of awareness of the local community about the potential of the village. Apart from that, Dadap village is a new village resulting from the division of Sugian village so that many outsiders are not familiar with the existence of Dadap village, including the tours in Dadap village. The purpose of this service is to introduce and empower tourism, especially Dadap beach, and also empower the community. By adding tourist facilities and making people aware of the importance of maintaining tourist destinations. The method of activity through the main work program carried out by KKN students in Dadap village is making directions for tourist sites, making trash cans, making photo spots in tourist areas, and tourism branding. Then for additional work programs, namely teaching the Koran, gymnastics, mutual cooperation, posyandu, and socializing the protection of tourism laws. The results of the activities during the KKN are the implementation of all the work programs that have been prepared. KKN students have made directions to three beaches, namely Dadap beach, Kubur Butun beach, and Ujung beach. Apart from that, KKN students were also able to set up beautiful photo spots on Dadap beach in the form of a gate with the words ‘Beach Desa Dadap’ which are exposed to match the blue sky. KKN students also carry out mutual cooperation on the beach and invite the community to keep the beach clean. To make things easier for the community, KKN students made trash bins along with holes for garbage disposal on Dadap beach. Broadly speaking, KKN students have achieved their goals.